Synthesis of a stable magnesium-impregnated biochar and its reduction of phosphorus leaching from soil. (May 2018) - Chen, Qincheng; Qin, Jiaolong; Cheng, Zhiwen; Huang, Lu; Sun, Peng; Chen, Lu; Shen, Guoqing
Abstract: Biochar improves soil fertility and promotes long-term terrestrial carbon sequestration. However, biochar seems not to be stable enough due to physical, chemical and biological reactions. In this study, a novel, stable, and magnesium (Mg)-impregnated biochar was prepared from cow dung and applied to decrease P leaching from soil. XPS, FTIR, XRD, SEM and EDS were used to evaluate the effect of modification and phosphorus(P) sorption on the oxidation resistance of biochar. The results showed that the oxidation resistance of the Mg-impregnated biochar was improved by the formation of MgO on its surface. The soil column experiment indicated that the Mg-impregnated -biochar decreased P loss from leaching by 89.25%. In addition, the available P content of the soil surface layer under Mg-impregnated biochar treatment increased by 3.5-fold relative to that under the control treatment. P sorption also enhanced the oxidation resistance of biochar. The relative contents of CO, CO, and COOH on the surface of P-laden biochar was 20.97% and was lower than those on the surface of biochar without P sorption (33.15%). Oxidation resistance was enhanced by the formation of new MgP crystals, which prevented the oxidation of CC, CC, and CH into CO, CO, and COOH, respectively, by acting as a physical barrier between the biochar surface and oxygen. The results of XRD, SEM and EDS provided evidence for the formation of MgP crystals. Overall, results indicated that the Mg-impregnated biochar can reduce P leaching loss from soil and has enhanced stability. Graphical abstract: Image 1 Highlights: A novel and stable engineered biochar was synthesized from cow dung. Amendment with engineered biochar increased P in the soil surface layer by 3.5-fold. Amendment with the engineered biochar decreased P leaching from soil by 89.25%. P sorption enhanced the oxidation resistance of biochar.